Saartjie by Hendrik Hofmeyr : sign systems and context - Olsen, Andrew Nicolas (North-West University (South Africa), Potchefstroom Campus, 2017)
The main aim of this dissertation is to investigate how context is constructed in Hendrik Hofmeyr's opera Saartjie through the verbal and non-verbal sign systems. In this qualitative study, I have followed a combined interpretivist and constructivist perspective. Saartjie focuses on the final night of Saartjie Baartman's life in Paris, while she reminisces about her life she left behind in South Africa to travel abroad. The opera and libretto is composed from Saartjie's perspective and, as a result of this, an anachronic and verbal narrative is presented to the audience. Through this type of presentation extratextual information is presented in the form of intertextualities, among others. Apart from Saartjie the character, the orchestra also non-verbally communicates ideas and concepts through the orchestra's speaking ability (Sprachvermögen) and this adds to the complexity of presenting various contexts in the opera. The orchestra's Sprachvermögen creates actants, which are not physically observable on the stage but essential to support the anachronic narrative to aid in the construction of various temporalities and spatialities in the text. In the text, various leitmotifs are employed, which not only support the constructions of context in the text but also binds the opera into an interconnected whole. The concept of what a text constitutes is broadened in line with Derrida's poststructuralist notion that everything can be considered a text. By interpreting the text, it becomes possible to make sense of the human experiences and contexts, which, in turn, needs to be decoded to be understood. Saartjie moved away from being a work - which is considered a static entity - to become a text through the process of the close reading and decoding the sign systems found in the opera. The data in this study will be analysed through a close reading, which falls within the paradigm of hermeneutics. I have made use of close reading as a strategy to discern the underlying meanings of Saartjie; this is, in turn, shared with the reader throughout the course of this dissertation. Other qualitative research methods include the use of interviews and questionnaires to corroborate the findings that arose during the course of this study. Furthermore, the sign systems in the text at the hand of Peirce's semiotic theory was also utilised. I have purposefully chosen Peirce's semiotic theory to interpret the signs in the text because Peirce's theory takes human feelings and psychology into account when interpreting signs. In this study, I have concluded that there are three main factors upon which context rests. These are temporality, spatiality, and the ideological zeitgeist. These three factors are brought to the fore through the verbal and non-verbal sign systems present in Saartjie and, as a result of this, these sign systems had to be decoded to understand their deeper meaning and contribution to context. I have used techniques in this study which are found in poststructuralism and literary theory and demonstrated that these theories can be fruitfully applied in the analysis of an operatic text as well
MMus (Musicology), North-West University, Potchefstroom Campus, 2017
Keywords: Saartjie Baartman; Hendrik Hofmeyr; Saartjie; Hermeneutics; Sign systems; Decoding; Otherness; Text; Context; Semiotics; Orchestral Sprachvermögen; Actants; Leitmotifs; Textual analysis; Close reading